Standardizing Qualifications and Criteria for the Selection, Certification, and Evaluation of Philippine Coast Guard K9 Handlers’ Instructors - Narvasa, Rene Leandro B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study examines the current qualifications of the Philippine Coast Guard (PCG) K9 Instructors in terms of eligibility, educational background, professional experience, rank, and training, and explores perspectives from select K9 instructors and officers of the PCG K9 Training Center on the required competencies specific to K9 instructors and the existing evaluation practices. Findings reveal that current tools for evaluation rely on generic measures and fall short in assessing behavioral competencies such as technical skills, kennel management, scenario-based training, and ethical handling of dogs. Similarly, feedback in the tool is a one-way process and is incapable of utilizing the results for the development of practice. These gaps risk mismatched qualifications, reduced instructional effectiveness, and negative impacts on student learning and ultimately on operational goals such as public safety, order, and trust.  Moreover, this study highlights the best practices of the Philippine National Police (PNP), the Philippine Drug Enforcement Agency (PDEA), the Philippine Army (PA), and two private K9 providers in their K9 Instructors, handler training, selection, and evaluation.  Based on these insights, the study proposes a standardized and systematized framework for selection, certification, and evaluation of PCG K9 Instructors, along with an enhanced performance tool. The findings aim to inform future improvements in PCG K9 curriculum and training standards.